Analysis of the Voltage Stability of Power Using L-Index Voltage Stability - Djami Olii; Eddy Djubir Kembuan; Joucke Rapar; Agus Takaredase (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Voltage stability is highly dependent on the ability of the system to maintain voltage conditions throughout the bus, both under normal conditions and after a disturbance. One static analysis tool often used is the power flow completion method to determine the voltage magnitude at several points under review. This paper presents static voltage stability analysis for heavy and light load conditions on the load bus. Voltage stability analysis is performed on the IEEE-14 power system bus using the L-index voltage stability method. L-index values ranging from 0 – 1, buses with L-index voltage stability values close to 1.0 are identified as critical buses.